2006
DOI: 10.1099/jmm.0.46580-0
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-associated oxidant monochloramine induces reactivation of Epstein–Barr virus (EBV) in gastric epithelial cells latently infected with EBV

Abstract: To investigate the possibility of an interaction between two ubiquitous human pathogens, Helicobacter pylori and Epstein-Barr virus (EBV), the effect of monochloramine (NH 2 Cl), locally produced by H. pylori infection, on gastric epithelium latently infected with EBV was examined, by assessing the induction of EBV lytic infection. AGS cells harbouring latently infected EBV were used as the indicator of lytic change caused by NH 2 Cl treatment. Lytic infection, determined by morphological change and EA-D antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…In fact, several studies that address the effect and interaction between them do not detected any association [20, 23, 4649]. However, there are others publications showing synergism between EBV and H. pylori in the pathogenesis of gastric diseases [30, 5053]. In point of fact, it is suggested two possible mechanisms, first an additional inflammatory response in co-infection and increased tissue damaging by both H. pylori and EBV.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies that address the effect and interaction between them do not detected any association [20, 23, 4649]. However, there are others publications showing synergism between EBV and H. pylori in the pathogenesis of gastric diseases [30, 5053]. In point of fact, it is suggested two possible mechanisms, first an additional inflammatory response in co-infection and increased tissue damaging by both H. pylori and EBV.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we identify, to our knowledge for the first time, a microbial protein from P. falciparum, that can drive a latently infected B cell into viral replication. Previous studies by Minoura-Etoh et al demonstrated that monochloramine (NH 2 Cl), a Helicobacter pylori–associated oxidant, induces viral production in epithelial cells [26]. …”
Section: Discussionmentioning
confidence: 99%
“…These genes are commonly found altered in various cancer types including GC [270]. Further, H. pylori positive individuals show a significantly higher EBV DNA load which suggests H. pylori role in lytic phase conversion of EBV [271]. Also, EBV DNA load was more in H. pylori positive patients than those uninfected with GC [272].…”
Section: Ebv and H Pylori Factors Contributing To The Developmentmentioning
confidence: 99%